Community Empowerment Model Based on Islamic Education Institutions - Muhammad Imam Hanif; Zulfa Mutakin (Al-Hayat: Journal of Islamic Education, 2019)
The problem of community empowerment, especially among the middle class, is a critical issue for the government in achieving the success of the development. If in the early 1970s few social movements and government groups were actively concerned and capable of dealing with developmental issues, now the situation is much in tandem with the establishment of thousands of NGOs (non-governmental organisations). The emergence of one of the typologies of non-governmental organisations with the background of Islamic educational institutions involving Kiai and several santri as the backbone of the organisation became one of the forms of innovation of Islamic educational institutions which aimed to empower the community. One of the NGOs with Islamic education background is the Pesantren and Society Development Bureau (BPPM) Pesantren Maslakul Huda (PMH) Kajen Margoyoso Pati founded by Kiai M.A Sahal Mahfudh who is active in community empowerment action in the country.Masalah pemberdayaan masyarakat terutama masyarakat kalangan menengah kebawah merupakan masalah yang sangat penting bagi pemerintah dalam mencapai keberhasilan pembangunan. Jika pada awal tahun 1970-an hanya sedikit gerakan sosial dan kelompok pemerintah yang secara aktif peduli dan mampu menangani masalah pembangunan, kini keadaan tersebut sudah jauh berbeda dengan berdirinya ribuan Lembaga Swadaya Masyarakat (LSM). Munculnya salah satu tipologi LSM yang berlatar belakang lembaga pendidikan Islam dengan melibatkan Kiai serta sejumlah santri sebagai tulang punggung organisasi, menjadi salah satu bentuk inovasi lembaga pendidikan Islam yang bertujuan untuk memberdayakan masyarakat. Salah satu LSM yang berlatarbelakang lembaga pendidikan islam adalah Biro Pengembangan Pesantren dan Masyarakat (BPPM) Pesantren Maslakul Huda (PMH) Kajen Margoyoso Pati, Jawa Tengah yang didirikan oleh Kiai M.A Sahal Mahfudh yang berkiprah dalam aksi pemberdayaan masyarakat di Tanah Air.